Perspektif Mahasiswa Muslim FKIP Universitas Mataram terhadap Ajaran Islam dalam Tradisi “Nyongkolan” sebagai Bagian dari Prosesi Pernikahan Masyarakat Adat Sasak Lombok - Lenny Herlina (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
Nyongkolan is one of the processions in a series of wedding traditions of the Sasak tribe of Lombok, West Nusa Tenggara. As a culture that is preserved in the midst of a majority Muslim community, the tradition of Nyongkolan which is carried out with great fanfare, in the form of a bridal procession escorted by the family and community as well as a musical group is interpreted as part of the teachings of the Prophet Muhammad where a marriage must be witnessed and also contains the value of friendship. However, there are several conditions where the implementation of Nyongkolan as a whole violates Islamic teachings, such as the clothes used, the situation where men and women are mixed, as well as the music, singing and dancing that are performed. This study aims to find out the perspectives of Muslim students regarding the implementation of the Nyongkolan tradition. whether in accordance with Islamic values and teachings or not, and must be preserved or not. The method used in this research is descriptive qualitative involving 280 students of FKIP University of Mataram batch 2022 as research subjects using a random sampling technique. The results of the study found that 100% of Muslim students stated that the Nyongkolan tradition was not in accordance with Islamic law, 92% stated that the Nyongkolan tradition could be carried out and preserved with the condition that the clothing used complies with Islamic rules, men and women are separated, music is replaced with drums or tambourines, as well as singing and dancing or dancing abolished. Meanwhile, 8% of students stated that the Nyongkolan tradition should be abolished because it is difficult to change according to the provisions of Islamic teachings. The implication of this research is that it can be concluded that Muslim students have a fairly good understanding of Islamic teachings, both with regard to values, morals and understand how to analyze how far a tradition is considered in accordance with Islamic teachings or not. This research is expected to be used as a consideration for the implementation of the next Nyongkolan.